INTERNATIONAL EXPERIENCE IN LEGALIZING SHADOW BUSINESS AND POSSIBILITIES FOR IMPLEMENTATION IN UKRAINE (Development Service Industry Management, 2025)
This article examines the shadow economy as a global problem that negatively impacts public finances, distorts the competitive environment, and hinders stable economic growth and effective social development in Ukraine. It's identified that the primary factors contributing to the shadow economy are high tax burdens, complex regulations, corruption, and a low level of trust in state institutions. The study aims to analyze international experience and economic mechanisms for legalizing shadow business, subsequently developing well-founded recommendations for Ukraine. The paper reviews successful and unsuccessful practices from various countries (Italy, Ireland, Indonesia, Georgia, Singapore, Estonia) that have employed tax amnesties, deregulation, fiscal transparency, and anti-corruption measures. It outlines the key roles of the state, business, and civil society in the legalization process and assesses the positive impact of de-shadowing on economic development. Special attention is given to innovative approaches, such as the use of digital technologies (blockchain, e-governance, Big Data, cashless payments) and international cooperation. Based on an analysis of Ukraine's experience (tax amnesties 2021-2023, deregulation, "Diia" application development), the study finds that some mechanisms have had limited effectiveness due to fragmentation, low trust, and an imperfect judicial system. A comprehensive approach is proposed for Ukraine, combining systemic reforms, enhanced digitalization, strengthening legal protection, and improving tax culture, drawing on best international practices.
Keywords: shadow economy; business legalization; tax amnesty; deregulation; anti-corruption; digitalization; international experience; economic development